Multidrug resistant and sensitive strains of Pseudomonas aeruginosa: Establishing clonal relationship by Pulsed Field Gel Electrophoresis and in vitro antibiotic synergy testing by E test - Mohd Nawi, S.F.A.; Karunakaran, R.; Thong, Kwai Lin; Yusof, M.Y.; Vadivelu, J. (Elsevier, 2010)
Background: The emergence of multidrug resistant Pseudomonas aeruginosa (MDRPA) as one of the leading nosocomial pathogens imposes a serious health threat due to limited antibiotic options. In this study, a sample of clonally distinct MDRPA and sensitive strains of Pseudomonas aeruginosa (SSPA) were tested against various antibiotics combinations to establish synergistic activity against these strains.